The first reported case of a deletion of the entire RPGR gene in a family with X-linked retinitis pigmentosa. (3rd September 2022) - Mihailovic, Nataša; Schimpf-Linzenbold, Simone; Sattler, Inga; Eter, Nicole; Heiduschka, Peter
ABSTRACT: Clinical phenotypes of a patient with a deletion of the entire RPGR gene have not been described in the literature yet. We hereby report a new mutation in a family of X-linked retinitis pigmentosa (×lRP), showing the deletion of the entire RPGR gene. Gene therapy for inherited retinal diseases holds great promise; however, so far there has been no approved treatment of RPGR -mediated retinitis pigmentosa. The presented evidence of genotype–phenotype correlation may be useful for genetic diagnosis or even genetic treatment in the near future.